ATR-Mediated Global Fork Slowing and Reversal Assist Fork Traverse and Prevent Chromosomal Breakage at DNA Interstrand Cross-Links - Mutreja, Karun (Cell Rep, 2018)
Interstrand cross-links (ICLs) are toxic DNA lesions interfering with DNA metabolism that are induced by widely used anticancer drugs. They have long been considered absolute roadblocks for replication forks, implicating complex DNA repair processes at stalled or converging replication forks. Recent evidence challenged this view, proposing that single forks traverse ICLs by yet elusive mechanisms. Combining ICL immunolabeling and single-molecule approaches in human cells, we now show that ICL induction leads to global replication fork slowing, involving forks not directly challenged by ICLs. Active fork slowing is linked to rapid recruitment of RAD51 to replicating chromatin and to RAD51/ZRANB3-mediated fork reversal. This global modulation of fork speed and architecture requires ATR activation, promotes single-fork ICL traverse—here, directly visualized by electron microscopy—and prevents chromosomal breakage by untimely ICL processing. We propose that global fork slowing by remodeling provides more time for template repair and promotes bypass of residual lesions, limiting fork-associated processing.